Changes in Composition of the Gut Bacterial Microbiome after Fecal Microbiota Transplantation for Recurrent Clostridium difficile Infection in a Pediatric Heart Transplant Patient - Flannigan, Kyle L.; Rajbar, Taylor; Moffat, Andrew; McKenzie, Leanna S.; Dicke, Frank; Rioux, Kevin; Workentine, Matthew L.; Louie, Thomas J.; Hirota, Simon A.; Greenway, Steven C. (Frontiers in Cardiovascular Medicine, 2017)
The microbiome is increasingly recognized as an important influence on human health and many of the comorbidities that affect patients after solid organ transplantation (SOT) have been shown to involve changes in gut bacterial populations. Thus, microbiome changes in an individual patient may have important health implications after SOT but this area remains understudied. We describe changes in the composition of the fecal microbiome from a pediatric heart transplant recipient before and >2.5 years after he underwent repeated fecal microbiota transplantation (FMT) for recurrent Clostridium difficile infection (CDI). With both documented episodes of CDI there was marked loss of bacterial diversity with overgrowth of Proteobacteria (>98.9% of phyla identified) associated with symptomatic colitis that was corrected after FMT. We hypothesize that a second CDI occurring after FMT was related to incomplete restoration of normal bowel flora post-FMT with relative deficiencies of the phyla Firmicutes and Bacteroidetes and the Families Lachnospiraceae and Ruminococcaceae. Following the second FMT there was a gradual shift in gut bacterial composition coincident with the recipient developing lymphonodular hyperplasia of the colon and painless hematochezia that resolved with discontinuation of mycophenolate mofetil (MMF). This case documents dynamic changes in the bacterial microbiome after FMT and suggests that MMF may influence the gut microbiome with consequences for the patient.